ACMEOLOGICAL COMPETENCE OF THE FUTURE HIGHER EDUCATION TEACHER: STRUCTURE AND CONTENT - Protsenko, Olena (Educological discourse, 2019)
The modern Ukrainian system of education requires updating of the content, methods, forms and means of training. Higher education institutions are faced with the problem to train teachers to work in the context of education system modernization, the use of the innovative educational technologies, the formation of competent, responsible higher education teacher, which is ready for permanent professional self-development, social and professional mobility. That is why the development of acmeological competence is necessary during the training of future specialists, which promotes the teacher’s self-development throughout the life.The article defines the meaning of the term «acmeological competence», which is characterized as a multicomponent structure, which provides the future higher education teacher’s orientation to professional self-development, achievement of his own acme in professional activity. The basic components of acmeological competence are identified: motivational and value components (achieving the professional acme, understanding the value of knowledge and acquired qualifications); cognitive (knowledge in acmeology, computer science, in the professional subjects); procedural component (skills for lifelong learning, professional and pedagogical skills); personality-reflexive component (characteristic, individual-psychological and reflexive-correcting skills). The defining of components of the acmeological competence makes possible to specify the essence of its concept and to determine methods and forms of organization of future teachers training in order to achieve a high level of development of each component and acmeological competence as a whole.